Developing the Potential of Creative Industries in the Field of Local Wisdom-Based Culinary Tourism in Lake Toba Tourism, North Sumatra - Putri Kemala Dewi Lubis; Firman Saputra; Abed Nego Siregar; Sarah Lylia Saragi (CV Projurnal Mitra Publikasi, 2025)
This study examines the development of culinary tourism in Toba Samosir Regency, North Sumatra, as a crucial component of the creative industry sector. The region's distinctive Batak cuisine, exemplified by dishes like arsik fish, represents a unique intersection of cultural heritage and economic opportunity. Through analysis of local culinary practices, cultural traditions, and tourism development initiatives, this research demonstrates how traditional gastronomy serves as both a cultural identifier and an economic driver. The study finds significant potential for culinary tourism development in Toba Samosir, supported by the region's rich local wisdom and the Indonesian government's strategic focus through the Office of Tourism and Creative Economy. This research highlights how the preservation and promotion of indigenous culinary practices can enhance tourism development while maintaining cultural authenticity, creating sustainable economic opportunities for local communities.